2019
DOI: 10.1038/s42003-019-0485-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome signature of autism in the human prefrontal cortex

Abstract: Autism spectrum disorder (ASD) is a common neurodevelopmental disorder with yet incompletely uncovered molecular determinants. Alterations in the abundance of low molecular weight compounds (metabolites) in ASD could add to our understanding of the disease. Indeed, such alterations take place in the urine, plasma and cerebellum of ASD individuals. In this work, we investigated mass-spectrometric signal intensities of 1,366 metabolites in the prefrontal cortex grey matter of 32 ASD and 40 control individuals. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 61 publications
3
41
0
Order By: Relevance
“…Amino acid signatures of oxidative stress and mitochondrial function are also present in our dataset. Dysregulated amino acid degradation, homeostasis, and import into the brain have been implicated as a cause of neuronal stress in ASD, and supporting metabolomic data has shown perturbations of various amino acid pathways, such as glutamate, methionine, glutathione, and gamma-glutamyl metabolites (10,17,24,26,29,33,49,52,76), which exhibit differences as well ( Figure 4E). We also demonstrate correlations between pathways of oxidative stress (cysteine, methionine, SAM and glutathione pathways) with the ADOS-SS ( Figure 4F).…”
Section: Asd Correlates With Cellular Energy and Oxidative Stress Metsupporting
confidence: 55%
See 2 more Smart Citations
“…Amino acid signatures of oxidative stress and mitochondrial function are also present in our dataset. Dysregulated amino acid degradation, homeostasis, and import into the brain have been implicated as a cause of neuronal stress in ASD, and supporting metabolomic data has shown perturbations of various amino acid pathways, such as glutamate, methionine, glutathione, and gamma-glutamyl metabolites (10,17,24,26,29,33,49,52,76), which exhibit differences as well ( Figure 4E). We also demonstrate correlations between pathways of oxidative stress (cysteine, methionine, SAM and glutathione pathways) with the ADOS-SS ( Figure 4F).…”
Section: Asd Correlates With Cellular Energy and Oxidative Stress Metsupporting
confidence: 55%
“…These most discriminatory metabolites were primarily from the lipid, amino acid, xenobiotic, and cofactor/vitamin super pathways ( Figures 1E-1F). Several of these metabolites have been previously linked to ASD, such as steroids, bile acids, acyl-carnitines, and nicotinamide metabolites (46)(47)(48)(49). Further, multiple molecules known to be produced or manipulated by the gut microbiota also featured prominently, including 4-ethylphenyl sulfate (4EPS), which is elevated in an ASD mouse model, and indolelactate, a microbe-derived tryptophan metabolite ( Figure 1E) (50,51).…”
Section: Plasma and Fecal Metabolomes Differ Between Asd And Tdmentioning
confidence: 97%
See 1 more Smart Citation
“…One of the functions of CysGly is a prooxidant that reduces ferric iron to ferrous iron [50]. Kurochkin et al (2019) observed that within the glutathione pathway, in addition to the decrease in the glutathione intensity, two metabolites, such as L-cysteinylglycine and L-γ-glutamyl-L-cysteine, display intensity differences in ASD [51]. Enzymes catalyzing reactions involving glutathione, L-cysteinylglycine, and L-γ-glutamyl-L-cysteine were shown to contain genetic variants connected with ASD (polymorphisms in genes such as GPX1, GSTM1, GGT1, and GSS51-53).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics perturbations associated to ASD cannot be only detected in blood, urine or saliva, but even in cerebellum or cortex samples of affected patients. In the study of Kurochin et al, 1366 metabolites were compared in the prefrontal cortex grey matter of ASD patients and healthy controls, revealing different profiles and metabolic pathways and opening the way to different analysis strategies [113].…”
Section: Metabolomics and Neuropsychiatric Disordersmentioning
confidence: 99%